To etch or not to etch, Part I: On the fatigue strength and dentin bonding performance of universal adhesives. Issue 6 (June 2021) - Stape, Thiago Henrique Scarabello; Viita-aho, Tapio; Sezinando, Ana; Wik, Patrik; Mutluay, Murat; Tezvergil-Mutluay, Arzu
Abstract: Objective: To characterize whether the bonding performance and fatigue strength of resin-dentin interfaces created by a universal adhesive would be affected by different H3 PO4 -application times to more accurately assess long-term durability. Methods: Mid-coronal flat dentin surfaces with standardized smear-layers were produced on sound third molars, etched with 32% H3 PO4 for 0, 3 and 15 s, bonded with a mild universal adhesive (3M-ESPE) and restored with a nanofilled composite. Bonded specimens (0.9 × 0.9 mm) were stored in deionized water for 24 h and sectioned into beams for microtensile testing (n = 10). Resin-dentin beams were tested under tension until failure (0.5 mm/min) after 24 h or 6 month storage in artificial saliva at 37 ̊C. Bar-shaped resin-dentin beams (0.9 × 0.9 × 12 mm) were tested under 4-point-flexure initially at quasi-static loads (n = 22) and then under cyclic loads (n > 50). The stress-life fatigue behavior was evaluated using the twin-bonded interface approach by the staircase method at 4 Hz. Fractured interfaces and the tension side of unfractured beams were evaluated under SEM, along with the micro-morphology of the etched dentin surfaces and hybrid layers. Data were analyzed by ANOVA and Tukey test and Wilcoxon Rank Sum Test ( α = 0.05). Results: Quasi-static loads were limited to discriminate the bonding performance of resin-dentin interfaces. Application modes significantly affected etching patterns, fatigue strength, endurance limits and hybrid layer morphology ( p < 0.001). Significance: Reductions in fatigue strength of self-etched bonded interfaces raise concerns about the true ability of universal adhesives to properly bond to dentin.